SISTEM PENUNJANG KEPUTUSAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK MENENTUKAN PERINGKAT SISWA TERBAIK PADA MADRASAH DINIYAH MIFTAHUL HUDA SERANG - Faradilla; Muhamad Sohari (Universitas Muhammadiyah Banten, 2026)
The aim of this paper is to design and develop a system that supports decision making in selecting the best students and evaluating the effectiveness of its implementation. The expected benefit is the creation of a more accurate and efficient selection process, ensuring that the best students have the potential and qualifications according to the needs of Madrasah Diniyah Miftahul Huda Serang. Madrasah Diniyah Miftahul Huda Serang faces challenges in determining the ranking of the best students because the selection process is carried out manually, which is prone to errors and less efficient. This research aims to develop a Decision Support System (DSS) using the Simple Additive Weighting (SAW) Method to increase objectivity and efficiency in assessment. The SAW method allows a more systematic assessment based on previously established criteria. This research focuses on the process of ranking the best students at Madrasah Diniyah Miftahul Huda Serang and the development of SAW-based SPK. The implementation of information technology is expected to increase accuracy and efficiency in the student selection process.